Is tooth wear a reliable means of aging wild European fallow deer in Tasmania, Australia? - Graham P. Hall; Peter J. Murray; Matthew J. Byrne; Allan T. Lisle (Wildlife Society Bulletin)
Abstract The tooth eruption and wear (TEW) technique for aging wild European fallow deer (Dama dama dama) in Tasmania, Australia has been in use for >15 yr, but it is also subjective and relies on the skill of the assessor and their assumptions of tooth wear. Deer managers and hunters have suggested that the TEW patterns observed in Tasmania are not consistent with age predictions of deer based on male antler growth. The cementum annuli (CA) technique provides a more objective assessment of age, but is more costly to perform. Our objective was to examine the relationship between the TEW and CA techniques for estimating the age of wild fallow deer in Tasmania. A game manager experienced in the use of the TEW technique assigned 300 deer jawbones collected from 3 sites during the 2001–2006 hunting seasons in Tasmania to different age categories. We conducted preliminary trials to develop a protocol that reliably exposed the CA in incisor teeth. Finally, we compared the ages determined by both methods. The preliminary trials successfully developed a protocol to use incisor teeth for reliably assessing CA. The CA technique gave a higher putative age than the TEW technique, though the magnitude of this result was dependent on location. The amount of soil ingested by the animals, and whether the animals mainly browsed or grazed were possible reasons why tooth wear varied between locations. Whilst the CA method is effective at indicating the age of wild deer, the method should be proven against known‐aged deer before being offered as a definitive measure of age. Managers should be clear in their objectives whether they require an approximate guide to age or an objective measure of age before deciding on which method to use. © 2011 The Wildlife Society.